Understanding the Urban Sharing Economy (Edward Elgar Publishing Ltd., 2025)
This book considers the potential solutions that the sharing economy offers to tackle the increasing challenges of urbanisation and sustainability facing cities. It emphasises the need for robust policies to ensure that the sharing economy supports urban sustainability and resilience by promoting more efficient and circular use of urban resources through practices like car-sharing, accommodation rentals, and the sharing of physical goods.
Keywords: Cities And The Sharing Economy; Governance Mechanisms; Institutionalisation; Sharing Business Models; Sharing Platforms; Sustainability Impacts